PEMANFAATAN EKSTRAK BELIMBING WULUH DAN EKSTRAK KULIT BUAH NAGA DALAM PEMBUATAN SELAI - Nurul Aini; Dody Handito; Siska Cicilia (Universitas Muhammadiyah Mataram, 2021)
This study aims to determine the concentration of starfruit juice and dragon fruit peel on the quality of jam. The experimental design used was a one-factor Randomized Block Design (RAK) with six treatments and three replications to obtain 18 samples. The treatments were the concentration of starfruit juice and dragon fruit peel extract with P1 (100% : 0%), P2 (85% : 15%), P3 (70% : 15%), P4 (55% : 45%), P5 ( 40% : 60%) and P6 (25% : 75%). Parameters observed were vitamin C levels, antioxidant activity, spread, and color as well as sensory tests (color, aroma, and taste). Data analysis results were tested by analysis of variance at a significance level of 5% using Co-Stat software. If there is a significant difference, then the orthogonal polynomial further test is carried out, while the physical and sensory tests are further tested using the Honest Significant Difference test at a significance level of 5%. The results showed that the concentration of star fruit juice and dragon fruit pulp did not have a different effect on vitamin C levels but had a significantly different effect on antioxidant activity, spread, and color. P6 treatment resulted in the highest antioxidant activity of 77.27%, 12.80 mg of vitamin C content, 10.1 cm of smearing power, and sensory properties that were acceptable to the panelists.